Development of multiplex polymerase chain reaction (PCR) assay for the simultaneous detection of vancomycin and linezolid resistant genes in enterococcus - Wada, Yusuf (2022)
Enterococci are Gram-positive cocci found in the guts of humans and animals. The introduction and dissemination of vancomycin-resistant Enterococcus (VRE) and Linezolid-Resistant Enterococcus (LZRE) in healthcare settings has increased patient management risks and difficulties. No multiplex PCR has been developed for the simultaneous detection of both vancomycin and linezolid resistant genes in Enterococcus. The goal of this research is to develop a multiplex PCR assay that can detect the Enterococcus genus, four VRE genes, and three LZRE genes all at the same time. Primers used in this study were specifically designed for the detection of vancomycin and linezolid resistant genes in Enterococcus. These genes are; 16S rRNA of Enterococcus genus, vanA – vanB – vanC - vanD for vancomycin, cfr methyltransferase, optrA and poxtA; an adenosine triphosphatebinding cassette (ABC) transporter for linezolid. A Vibrio cholerae ctxA (Internal amplification control) was included. Optimization of primer concentrations, MgCl2, dNTPs, Taq DNA polymerase and primers annealing temperature was also done. This was followed by evaluating the sensitivity and specificity of the optimized multiplex PCR and their analytical sensitivity both at the genomic and bacteria level. Final Primer concentrations was optimized as follows; 16S rRNA is 1.0 pmol/μl, vanA 1.0 pmol/μl, optrA 1.0 pmol/μl, cfr 1.0 pmol/μl, poxtA 0.1 pmol/μl, vanB 0.08 pmol/μl, ctxA 0.07 pmol/μl, vanC 0.8 pmol/μl and vanD 0.1 pmol/μl. Further, a MgCl2, dNTPs and Taq DNA polymerase optimized concentration was 2.5 mM, 0.16 mM and 0.75 units respectively. An annealing temperature of 64.5℃, a LOD of 100 pg at the genomic level and as low as 105 CFU/ml at the bacteria level were utilized and evaluated in the developed multiplex PCR assay. In this study, the sensitivity, specificity, NPV, PPV and accuracy of the developed multiplex PCR assay in the detection of VRE genes were 76.32% (CI: 59.76% - 88.56%), 100% (CI: 87.23% - 100.00%), 75% (CI: 62.90% - 84.15%), 100% and 86.15% (CI: 75.34% - 93.47%) respectively. Similarly, the sensitivity, specificity, NPV, PPV and accuracy of the developed multiplex PCR assay in the detection of LZRE genes were 88.89% (CI: 51.75% - 99.72%), 100% (CI: 86.77% - 100.00%), 96.30% (CI: 80.38% - 99.40%), 100% and 97.14% (CI: 85.08% - 99.93%) respectively. This developed multiplex PCR is sensitive, species-specific, rapid and capable of detecting vancomycin and linezolid resistant Enterococcus genes in clinical and environmental settings. The development of a multiplex PCR assay that will take into account all known VRE genes and linezolid mutation so that they would not be missed during routine laboratory diagnosis is highly recommended.